$50 mil woodchip farm: 200 NT jobs - Irby, Ross.
tag=1 data=$50 mil woodchip farm: 200 NT jobs tag=2 data=Irby, Ross tag=3 data=NT News tag=8 data=FORESTS tag=9 data=WOODCHIP VENTURETHURST ISLANDACIA TREES%TIWI LAND COUNCIL%SYLVATECH LTD%FORBIO GROUP tag=32 data=PALMER, MICK%TURVEY, NIGEL%EVERINGHAM, PAUL%BODEN, DAVID tag=34 data=PRSS tag=61 data=06 tag=62 data=Jun tag=63 data=1997